Web management system for serious game in internal medical practice - Yin, Phoon Wei (2013)
The project is to develop a web management system for serious game in internal medicine practice. The objective of this project is to develop a web management system for managing user’s data in serious game for internal medicine practice. In addition, the web management system can be functional in register, login, and logout, forgot password, change password, manage user, create patient profile, assign patient, delete patient profile and view log. There are some databases required for the web management system that is register table, patient table and assign table. XAMPP is the main software to develop the web management system. The web management system is using PHP as a server-side language and MySQL as database. The admin enables to use the web management system to manage user’s data in the serious game.